2022
DOI: 10.2147/jhc.s364703
|View full text |Cite
|
Sign up to set email alerts
|

Macrotrabecular-Massive Hepatocellular Carcinoma: Light and Shadow in Current Knowledge

Abstract: The subject of this narrative review is macrotrabecular-massive hepatocellular carcinoma (MTM-HCC). Despite their rarity, these tumours are of general interest because of their epidemiological and clinical features and for representing a distinct model of the interaction between the angiogenetic system and neoplastic cells. The MTM-HCC subtype is associated with various adverse biological and pathological parameters (the Alfa-foetoprotein (AFP) serum level, tumour size, vascular invasion, and satellite nodules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 56 publications
1
1
0
1
Order By: Relevance
“…Although some previous studies have focused on the clinical and radiological features of MTM-HCC, there is no consensus on the best biomarker for predicting MTM-HCC. Our study showed that MTM-HCC patients presented with large tumour sizes and high AFP loads, which were consistent with previous findings[ 17 - 20 ]. Interestingly, this study found that the age of patients with MTM-HCC was lower than that of the patients with nMTM-HCC.…”
Section: Discussionsupporting
confidence: 93%
“…Although some previous studies have focused on the clinical and radiological features of MTM-HCC, there is no consensus on the best biomarker for predicting MTM-HCC. Our study showed that MTM-HCC patients presented with large tumour sizes and high AFP loads, which were consistent with previous findings[ 17 - 20 ]. Interestingly, this study found that the age of patients with MTM-HCC was lower than that of the patients with nMTM-HCC.…”
Section: Discussionsupporting
confidence: 93%
“…Как и многие другие авторы, мы столкнулись с мимикрией этого варианта под ГЦК из-за характерных особенностей визуализации: гиперваскулярности, быстрого накопления контрастного препарата в артериальную фазу и сниженной плотности по отношению к сохранной паренхиме печени в отсроченную фазу контрастирования [3,13]. В связи с наличием в данном случае множественного поражения в виде «дочерних» опухолей, необходимо было исключить массивный тип ГЦК, который в литературе характеризуют наличием крупных фокусов поражения с возможным образованием сателлитных узлов (обычно без признаков цирроза) в окружающей паренхиме печени [14]. О возможности доброкачественного характера образования в нашем случае позволили думать признаки, так же описываемые рядом авторов: отсутствие быстрого вымывания (wash-out) контрастного препарата, характерного для ГЦК, наличие липоматозных участков, отсутствие накопления контрастного вещества капсулой [1,3,10,15].…”
Section: Discussionunclassified
“…A large number of studies have been conducted to identify the high-risk factors affecting early postoperative recurrence of HCC, such as tumor size, tumor number, tumor differentiation, MVI, AFP level and Protein Induced by Vitamin K Absence or Antagonist II (PIVKA-II) level [6,18,19]. However, there are few reports on the effect of the MTM-HCC HCC pathological type on early postoperative recurrence of HCC [8,9,14,15,20], and the predictive value of the histological type has not received much attention from the general public. MTM-HCC is more aggressive than other types of HCC, showing more vascular invasion (including large vessels and microvessels), low differentiation and high proliferation, and it is an independent risk factor for early recurrence and total recurrence [8,9].…”
Section: Discussionmentioning
confidence: 99%